Corak Tafsir Aqidah (Kajian Komparatif Penafsiran Ayat-ayat Aqidah) - Ahmad Atabik (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
This article seeks to describe the theological genre of Qur’anic exegesis with special reference to the comparative sudy on various Qur’anic exegesis towards theological verses. In the course of kalām (theology), there are plenty of  Islamic sects, those who involved in the debate of disputed theological issues, most notable of them are the Ash’arite and the Mu’tazilite. Their contention concerning theological issues has also affected the mufassir (Qur’anic exegetes), those who interpret the Qur’anic verses. Some problems which are previously not taken into consideration, gradually systematized, conceived, polarized, and even cause the contention among Islamic community. In this paper, i describe and analyze two issues on kalām discourse; the word of God (kalām Allāh) and ru’yatullāh (seeing God in heaven). In the disputes on both issues, i also provide the Qur’anic exegesis from Mu’tazilite, Asy’arite, and Salafi-Wahabi.[Artikel ini akan memaparkan tentang cora tafsir akidah dengan kajian spesifiknya komparasi penafsiran terhadap ayat- ayat akidah. Dalam kajian ilmu kalam (teologi), terdapat beberapa sekte yang banyak melakukan perdebatan dalam permasalahan kalam, yaitu Kaum Mu’tazilah dan Asyr’ariyyah. Pemikiran kedua sekte ini mengimbas kepada para mufassir (ahli tafsir) yang menafsirkan ayat-ayat al-Qur’an. Masalah-masalah yang dulunya tidak terfikiran, secara berangsur menjadi terfikirkan, tersistematisasi, terkonsepsi, dan terpolarisasi, bahkan acap kali berimplikasi pada pertengkaran antar umat Islam. Pada kajian ini, penulis setidaknya mendeskripsikan sealigus menganalisa dua tema perdebatan kalam, yaitu permaslahan kalam Allah dan ru’yatullāh (melihat Allah). Dalam perdebatan terhadap dua tema tersebut, penulis juga menyuguhan penafsiran dari sekte Mu’tazilah, Asy’ariyah, dan Salafi-Wahabi.]